Effect of MgO-HPAM nanocomposite on the rheological and filtration properties of water-based drilling fluids - Pu Cao; Ayat Hussein Adhab; Dharmesh Sur; Abhinav Kumar; Suhas Ballal; Abhayveer Singh; Anita Devi; Kamal Kant Joshi; Morug Salih Mahdi; Aseel Salah Mansoor; Usama Kadem Radi; Nasr Saadoun Abd; et al. (Scientific Reports)
Abstract This research explores the novel enhancement of water-based drilling fluids using MgO-HPAM nanocomposites, focusing on improving their rheological and filtration properties. The study introduces an innovative approach to address the critical challenges in drilling technologies, emphasizing the need for stable and efficient drilling fluids in the oil and gas industry. Unlike traditional formulations, MgO-HPAM nanocomposites leverage the synergistic interaction between MgO nanoparticles and hydrolyzed polyacrylamide (HPAM) to overcome limitations such as instability and poor fluid performance in high-pressure and high-temperature environments. By integrating MgO nanoparticles with HPAM, the study provides a sustainable and cost-effective solution to optimize drilling efficiency while reducing environmental impact. The findings reveal that MgO nanoparticles, when used in conjunction with HPAM, significantly improve the drilling fluid’s performance. At an optimal concentration of 500 ppm, the yield point increased by 43%, and viscosity rose by 35%, demonstrating superior rheological performance. Notably, these enhancements were achieved without altering the fluid density, a critical factor in wellbore stability. Additionally, the filtration rate was reduced by 40%, highlighting the nanocomposite’s ability to decrease permeability and improve fluid stability under harsh drilling conditions. Furthermore, long-term tests confirmed the stability of MgO-HPAM nanocomposites, proving their durability and compatibility with existing additives. The study concludes that MgO-HPAM nanocomposites offer a groundbreaking and scalable approach to advancing drilling fluid technology. However, concentrations above 500 ppm showed diminishing returns, with viscosity stabilization and a slight increase in filtration volume. Through this optimization-based investigation, the research presents a significant step forward in formulating drilling fluids that maximize operational efficiency, safety, and environmental sustainability.